2022
DOI: 10.1021/acs.jchemed.1c00675
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an At-Home, First-Semester Biochemistry Lab Course: A Module Based on Banana Tyrosinase

Abstract: This paper describes the development of a fully remote upper-class biochemistry lab course. The sudden change to online teaching in the middle of spring semester 2020 had a primarily negative impact on laboratory teaching. These effects were mitigated because the students had done many of the basic hands-on procedures before the switch. A true "at-home" biochemistry lab module was implemented in the fall semester of 2020 to ensure students could have a hands-on lab experience in a remote setting despite the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Though the concept of a hybrid lab course is not new, the development and implementation of a complete at-home biochemistry lab course is still novel, with only one recent example, and many individual experiments that provide effective low-cost solutions that could be practiced in a home setting. , Transitioning laboratory learning experiences to adapt to hybrid settings, as necessitated by recent shifts in educational modalities, presents both unique opportunities and challenges. At-home laboratories offer the advantage of convenience and flexibility, allowing students to engage in scientific inquiry in a familiar environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the concept of a hybrid lab course is not new, the development and implementation of a complete at-home biochemistry lab course is still novel, with only one recent example, and many individual experiments that provide effective low-cost solutions that could be practiced in a home setting. , Transitioning laboratory learning experiences to adapt to hybrid settings, as necessitated by recent shifts in educational modalities, presents both unique opportunities and challenges. At-home laboratories offer the advantage of convenience and flexibility, allowing students to engage in scientific inquiry in a familiar environment.…”
Section: Introductionmentioning
confidence: 99%
“…In biochemistry and biology courses, the use of model organisms is a well-established approach to teaching complex concepts and providing applied experiences (e.g., E. coli, Dictyostelium discoideum , Neurospora crassa , Saccharomyces cerevisiae , and C. elegans ). However, the accessibility, cost, and safety of some model organisms can be prohibitive. As educational institutions continue to adapt to hybrid learning environments, it is essential to develop innovative approaches to laboratory courses; thus, educators have been exploring alternative methods and resources for teaching laboratory-based courses, with a focus on practicality and accessibility. …”
Section: Introductionmentioning
confidence: 99%
“…Normally, colorimetric assays were carried out using spectrophotometers. However, nowadays, digital images obtained using electronic devices such as smartphones and scanners have been widely used instead of spectrophotometers. For example, Na + , F – , Fe 3+ , Cu 2+ , , NO 2 – , NO 3 – , tyrosinase, glucose, proteins, ,, food dyes, reducing compounds, and pharmaceuticals were quantified using digital images.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps it is no surprise that a large proportion of the chemical educational literature related to COVID-19 teaching covers the replacement of face-to-face laboratory courses with online alternatives . These include asynchronous recordings of experiments, synchronous viewing of experiments performed by an instructor in the laboratory, , being given sample data to analyze, , performing online simulations , and performing at-home experiments . In a seminal review by Kelley, it was found that many of these approaches offered limited evidence about how effective they were as replacements for face-to-face laboratories .…”
Section: Introductionmentioning
confidence: 99%